Repeat biopsy versus initial biopsy in terms of complication risk factors and clinical outcomes for patients with non-small cell lung cancer: a comparative study of 113 CT-guided needle biopsy of lung lesions - Wang, Yangyang; Zhang, Yongyuan; Ren, Nana; Li, Fangting; Lu, Lin; Zhao, Xin; Zhou, Zhigang; Gao, Mengyu; Wang, Meng (Frontiers in Oncology, 2024)
The safety and feasibility of repeat biopsy after systemic treatment for non-small cell lung cancer have received extensive attention in recent years. The purpose of this research was to compare complication rates between initial biopsy and re-biopsy in non-small cell lung cancer patients with progressive disease, and to assess complication risk factors and clinical results after re-biopsy. Methods: The study included 113 patients initially diagnosed with non-small cell lung cancer underwent lung biopsy at initial biopsy, and rebiopsy after progression while on epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and/or chemotherapy from January 2018 to December 2021. We compared the incidence of complications between initial biopsy and re-biopsy, and analyzed the predictors factors that influenced complications in patients who underwent re-biopsy. Results: Successful rate of re-biopsy was 88.5% (100/113). 98 patients maintained original pathological type, 2 cases lung adenocarcinoma transformation to small cell lung cancer after gefitinib treatment. Secondary EGFR T790M mutation accounts for 55.6% of acquired resistance. The total number of patients with complications in initial biopsy was 25(22.1%), and 37 (32.7%) in re-biopsy. The incidence of pulmonary hemorrhage increased from 7.1% at initial biopsy to 10.6% at re-biopsy, while the incidence of pneumothorax increased from 14.2% to 20.4%. Compared with initial biopsy, the incidence of overall complication, parenchymal hemorrhage, and pneumothorax increased by 10.6%, 3.5%, and 6.2%, respectively. In all four evaluations (pneumorrhagia, pneumothorax, pleural reaction, overall complication), there were no significant differences between the re-biopsy and initial biopsy (all p>0.05). The multivariate logistic regression analysis suggested that male sex (OR= 5.064, P =0.001), tumor size≤2cm (OR= 3.367, P =0.013), EGFR-TKIs with chemotherapy (OR= 3.633, P =0.023), and transfissural approach (OR= 7.583, P =0.026) were independent risk factors for overall complication after re-biopsy. Conclusion: Compared with initial biopsy, the complication rates displayed a slight, but not significant, elevation in re-biopsy. Male sex, tumor size≤2cm, transfissural approach and EGFR-TKIs combined with chemotherapy were independent risk factors for re-biopsy complications.